Beware of the "end contractualization!": Battle cry - Vicente B. Paqueo; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2016)
In the aftermath of the 2016 election, labor leaders and their political allies pushed for an immediate end to the so-called employment "contractualization", a policy proposal currently popular with voters and politicians. The idea is for the government to tighten and reduce, if not prohibit, the use of temporary employment contracts (TECs) and job outsourcing. This paper analyzes the policy idea and its potential economic consequences by looking at the roles of TECs and job outsourcing in the functioning of efficient labor markets, the experience of European countries regarding TECs, and Philippine employment data. The study finds that while the policy idea is anchored on good intentions, it can undermine the goal of achieving rapid, inclusive, and sustained economic growth. The realization of this outcome depends on the nature of the policy design actually adopted. On this point, the paper suggests a framework that can be useful in formulating a coherent policy on temporary employment and a strategy for dealing with "endo" practices.
Keywords: 330; Philippines; employment; jobs; labor market policy; contracts; contractualization; temporary employment contracts (TECs); job outsourcing; endo